ANALISIS PENANAMAN SIKAP SOSIAL MELALUI PEMBELAJARAN IPS PADA SISWA KELAS V DI SD NEGERI BONTORAMBA 1 KOTA MAKASSAR - kumaratungga, irmayanti; Afni, Nur; mulyadi, mulyadi (ALENA : Journal of Elementary Education, 2024)
This study aims to find out (1) to find out the description of the results of instilling social attitudes through social studies learning in students in class V (2) to find out the supporting and inhibiting factors in the social studies learning process carried out by the teacher in instilling social attitudes in class V students. This study used qualitative research. The object of his research was fifth grade students with a total of 16 students at SD Negeri Bontoramba 1 Makassar. Data analysis in this study is observation, interviews, questionnaires, and documentation. The results of the research conducted show that (1) The description of the process of cultivating students' social attitudes through social studies learning can be seen from the use of learning media and evaluation tools used by the teacher to assess students' social attitudes. (2) Supporting factors in instilling social attitudes by achieving learning to cultivate social attitudes applied by social studies learning teachers, there are almost no obstacles faced by teachers in teaching social attitudes (honesty, courtesy, self-discipline, tolerance and mutual help). Instilling Social Attitudes in Class V Students of SD Negeri Bontoramba 1 Makassar City has instilled the value of social attitudes in accordance with the indicators. It can be concluded that the cultivation of social attitudes through social studies learning in class V SD Negeri Bontoramba 1 Makassar City can be increased..